2001
DOI: 10.1263/jbb.91.94
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Long-Chain n-Paraffins from Waste Oil of Car Engine by Acinetobacter sp.

Abstract: Microorganisms that degrade long-chain n-paraffins from used car engine oil were isolated from soil. For the screening, a fraction of n-paraffin prepared from car engine oil was applied as the sole carbon source. The strain was identified as Acinetobacter sp. The ability of the strain to assimilate long-chain n-paraffins was assessed and characterized. The strain mineralized long-chain n-paraffins (0.1% w/v) in the minimal medium after cultivation for 96 h and also reduced the weight of the waste oil added (1%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…The presence of various crude oildegrading microorganisms corresponded to the contamination of petroleum hydrocarbons in Thai coastal areas (Wattayakorn, 2005). Although all of the tested microorganisms were able to grow in crude oil-NSW (Aluyor and Ori-jesu, 2009;Koma et al, 2001). To screen for the effi cient lubricant-degrading strains, the isolated microorganisms were characterized for their cellular properties.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of various crude oildegrading microorganisms corresponded to the contamination of petroleum hydrocarbons in Thai coastal areas (Wattayakorn, 2005). Although all of the tested microorganisms were able to grow in crude oil-NSW (Aluyor and Ori-jesu, 2009;Koma et al, 2001). To screen for the effi cient lubricant-degrading strains, the isolated microorganisms were characterized for their cellular properties.…”
Section: Discussionmentioning
confidence: 99%
“…Although the chemically inert alkanes are activated by the addition of fumarate (Heider et al, 1999;Widdel and Rabus, 2001;Wilkes et al, 2003) during anoxia, aerobic activation is accomplished by the terminal (Sepic et al, 1995;Koma et al, 2001;Van Hamme et al, 2003) or subterminal (Whyte et al, 1998;Kotani et al, 2006Kotani et al, , 2007 introduction of oxygen. For alkanes with a chain length oC 30 , which can be considered as typical for plant waxes, terminal oxygen introduction is mainly catalysed by the membrane bound, rubredoxin-dependent di-iron alkane monooxygenase (AlkB), which is found among Actinobacteria, a-, b-and g-Proteobacteria (van Beilen et al, 2003;van Beilen and Funhoff, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…strain M-1 has the ability to degrade a variety of n-alkanes, including very long-chain n-alkanes with carbon chain lengths of C 20 to C 44 at ambient temperature (Tani et al, 2001). In addition, Koma et al (2001) have also studied an Acinetobacter strain that can assimilate long-chain n-paraffins from the waste oil of car engines. Kotlar et al (2007) isolated and identified an Acinetobacter sp.…”
Section: Introductionmentioning
confidence: 99%